2010
DOI: 10.1159/000313483
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Levels of MMP2/TIMP2 and Cardiovascular Risk in CAPD Patients

Abstract: Background/Aims: Matrix metalloproteinases (MMPs), their inhibitors (TIMPs), oxidative stress (SOX) and kynurenine (KYN) pathway have been postulated in cardiovascular disease (CVD) progression. We hypothesized the possible association between the MMP/TIMP system, KYNs and CVD prevalence in continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: We assessed MMP-2, MMP-9, TIMP-1, TIMP-2, KYN and its metabolite – quinolinic acid (QA), and SOX marker – Cu/Zn superoxide dismutase (Cu/Zn SOD) levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
8
15
0
Order By: Relevance
“…In line with our results showing increased MMP-2 and TIMP-2 levels in ESKD patients, elevated circulating MMP-2 and TIMP-2 levels have been described as an indicator of CVD in dialysis patients [8,9]. It is possible that TIMP-2 levels increase in order to protect against abnormal proteolytic activity in patients on dialysis, which could promote excessive extracellular matrix remodeling, as previously suggested [9,15]. While most of the previous studies agree with our findings [8,10,11,12], two studies detected no significant changes in these markers [13,14], and one study showed lower TIMP-2 levels and augmented MMP-2/TIMP-2 ratios in ESKD [14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with our results showing increased MMP-2 and TIMP-2 levels in ESKD patients, elevated circulating MMP-2 and TIMP-2 levels have been described as an indicator of CVD in dialysis patients [8,9]. It is possible that TIMP-2 levels increase in order to protect against abnormal proteolytic activity in patients on dialysis, which could promote excessive extracellular matrix remodeling, as previously suggested [9,15]. While most of the previous studies agree with our findings [8,10,11,12], two studies detected no significant changes in these markers [13,14], and one study showed lower TIMP-2 levels and augmented MMP-2/TIMP-2 ratios in ESKD [14].…”
Section: Discussionsupporting
confidence: 89%
“…These alterations clearly promote vascular medial layer calcification [6], and the increases in MMP-2 levels correlated positively with vascular stiffness and phosphate concentrations in chronic kidney disease patients [25]. In line with our results showing increased MMP-2 and TIMP-2 levels in ESKD patients, elevated circulating MMP-2 and TIMP-2 levels have been described as an indicator of CVD in dialysis patients [8,9]. It is possible that TIMP-2 levels increase in order to protect against abnormal proteolytic activity in patients on dialysis, which could promote excessive extracellular matrix remodeling, as previously suggested [9,15].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These alterations clearly promote vascular medial layer calcification and the increases in MMP-2 level correlated positively with vascular stiffness and phosphate concentrations in CKD patients [8]. In line with our results showing increased MMP-2 level in uremic patients, the elevated circulating MMP-2 levels have also been described as an indicator of cardiovascular disease in HD patients [13,24]. Compared to MMP-2, very conflicting results on MMP-9 level in progressive CKD and ESKD patients have been reported (Table 5).…”
Section: Discussionsupporting
confidence: 88%
“…Among known MMPs, gelatinases (MMP-2, 72 kDa; MMP-9, 92 kDa) are the most studied because accumulated data show that both enzymes play important roles in the pathogenesis of cardiovascular diseases and CKD [4,8]. TIMPs (21)(22)(23)(24)(25)(26)(27)(28) are specific endogenous molecule that bind MMPs and inhibit MMPs activity [2]. TIMP-1, -2, -3 and -4, have been identified in humans and their expression is regulated during development and tissue remodeling [10].…”
Section: Introductionmentioning
confidence: 99%